Dynamics and related hazards of the Belvedere Glacier in the Italian Alps: a review - Jan Kropáček; Pragya Mehrishi; Irene Maria Bollati; Lukáš Brodský; Manuela Pelfini; Roberto Sergio Azzoni; Susanne Schmidt; Marcus Nüsser; Vít Vilímek (Acta Universitatis Carolinae Geographica)
The Belvedere glacier is an intensively studied glacier in the Italian Alps on the east face of the Monte Rosa, which is currently undergoing a fast deglaciation connected to various slope failures and Glacial Lake Outburst Floods. Measurements of the terminus position have been carried out since the 1920s. Since 2000, more attention has been paid to this area due to the occurrence of large mass movements and a surge-type event. In this review, research articles and various reports dealing mainly with glacier dynamics, rock and ice avalanches, Glacial Lake Outburst Floods, and other hazardous processes were considered. Aerial photogrammetry, Unmanned Aerial Vehicles, satellite stereo-processing and several terrestrial approaches (laser scanning, geophysics, measurements of near-surface heat flow, ablation stakes and camera-lapse) provided a base for quantifying the ongoing processes. Despite efforts based on the comparison of Digital Elevation Models, this review shows that the evolution of the Belvedere glacier in terms of ice volume is still partially unknown due to the low temporal frequency of aerial surveys, technical limitations of the Unmanned Aerial Vehicles used, and the fact that most studies focus only on the lower part of the glacier. The hazardous supraglacial Effimero lake that appeared during the surge-type event has been well documented, and interventions to mitigate potential risks were put in place, but the trigger of the event and the evolution of the lake basin have not yet been clarified. Mass wasting and outburst floods are mainly documented in the grey literature. The degradation of permafrost was suggested to be the driver of rock and ice avalanches, including one of the largest ice avalanches in the Alps, which occurred in 2005. In summary, the Belvedere Glacier and the surrounding rock walls have experienced repeated slope failures, an incident of surge and several outburst floods. Despite regular monitoring, a clear picture of its behavior due to the changing climate is still unknown. This review is intended to pave the way for further integrative studies.